In vitro Activity of Seaweed Extracts Collected from Gulf of Mannar Coast Islands Tamilnadu on Clinical Isolates - Sivakumar, S R (International Journal of Pharmaceutical & Biological Archive, 2014)
In vitro Activity of Seaweed Extracts Collected from Gulf of Mannar Coast Islands Tamilnadu on Clinical Isolates